2011
DOI: 10.1007/s10815-011-9573-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of common mechanisms between endometriosis and ovarian cancer

Abstract: Increased TGF-β1, COX-2, VEGF, ER-1α, AR, and aromatase and decreased PR in endometriotic as well as EOC cells suggests a potential association between these two disease processes. This association is important, as it may reveal common mechanisms for both diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 49 publications
0
11
0
3
Order By: Relevance
“…50 Indeed, the calculated risk of women developing ovarian cancer is two times higher compared with the general population, and after a follow-up period of over 10 years, this risk may increase 4.2-fold. 4,17 Although the ovary is the most affected organ by endometriosis-originated tumors, reports have recently showed that endometriosis is a risk factor for the development of endometrial cancer. 48,51 Even if infrequently, there have been reports of extraovarian sites affected by malignant transition from endometriotic implants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…50 Indeed, the calculated risk of women developing ovarian cancer is two times higher compared with the general population, and after a follow-up period of over 10 years, this risk may increase 4.2-fold. 4,17 Although the ovary is the most affected organ by endometriosis-originated tumors, reports have recently showed that endometriosis is a risk factor for the development of endometrial cancer. 48,51 Even if infrequently, there have been reports of extraovarian sites affected by malignant transition from endometriotic implants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have shown that molecules like the inflammatory cytokine Il-1, growth factors and TNF-α are expressed in endometriosis, creating a condition comparable to the one found in malignancies. 4,17,60 Another work has detected overexpression of p53 in atypical endometriosis and cancer associated with endometriosis by immunohistochemistry. The authors concluded that the molecule may be used to identify endometriosis with premalignant potential.…”
Section: Endometriosis' Malignant Transformation From the Molecular Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been associated with several types of cancer, such as pancreatic cancer (Wu et al, 2010), melanoma (Shahbazi et al, 2002), gliomas, and ovarian cancer, where it was shown that the presence of the G allele may be a protective factor for the development of this type of cancer (Araujo et al, 2009). Studies have shown that ovarian cancer may be related to endometriosis (Brinton et al, 1997(Brinton et al, , 2004Meng et al, 2011); thus, the +61 A/G EGF polymorphism may be involved in the mechanism of endometriosis development.…”
Section: Discussionmentioning
confidence: 99%
“…Additional potential biomarkers being elevated in endometriosis are TGF-β1, COX-2, VEGF, ER-1α and aromatase (Meng et al, 2011), but their elevated levels are unfortunately not fully endometriosis-specific to be utilized in clinical practice. Despite extensive research, co consensus exists on the use of cytokines in diagnosis (Fassbender et al, 2015).…”
Section: Immunological Markersmentioning
confidence: 99%